Exploring stachydrine: from natural occurrence to biological activities and metabolic pathways - He, Zekun; Li, Peng; Liu, Pan; Xu, Ping (Frontiers in Plant Science, 2024)
Stachydrine, also known as proline betaine, is a prominent constituent of traditional Chinese herb Leonurus japonicus, renowned for its significant pharmacological effects. Widely distributed in plants like Leonurus and Citrus aurantium, as well as various bacteria, stachydrine serves pivotal physiological functions across animal, plant, and bacterial kingdoms. This review aims to summarizes diverse roles and mechanisms of stachydrine in addressing cardiovascular and cerebrovascular diseases, neuroprotection, anticancer activity, uterine regulation, anti-inflammatory response, obesity management, and respiratory ailments. Notably, stachydrine exhibits cardioprotective effects via multiple pathways encompassing anti-inflammatory, antioxidant, anti-apoptotic, and modulation of calcium handling functions. Furthermore, its anti-cancer properties inhibit proliferation and migration of numerous cancer cell types. With a bi-directional regulatory effect on uterine function, stachydrine holds promise for obstetrics and gynecology-related disorders. In plants, stachydrine serves as a secondary metabolite, contributing to osmotic pressure regulation, nitrogen fixation, pest resistance, and stress response. Similarly, in bacteria, it plays a crucial osmoprotective role, facilitating adaptation to high osmotic pressure environments. This review also addresses ongoing research on the anabolic metabolism of stachydrine. While the biosynthetic pathway remains incompletely understood, the metabolic pathway is well-established. A deeper understanding of stachydrine biosynthesis holds significance for elucidating its mechanism of action, advancing the study of plant secondary metabolism, enhancing drug quality control, and fostering new drug development endeavors.